Voltage and frequency instability in large PV systems connected to weak power grid - Zhang, Qianjin; Hu, Qi; Sun, Siwei; Mei, Dikui; Liu, Sucheng; Liu, Xiaodong (Frontiers in Energy Research, 2023)
The voltage and frequency control of photovoltaic (PV) systems are influenced by coupled nonlinear factors. It has been discovered that frequency control stability is threatened by voltage regulation methods in PV systems. However, the frequency instability caused by voltage regulation methods has not been fully investigated. This paper investigates the voltage and frequency stability problems in PV systems connected with weak power grids. The voltage problems caused by grid impedance, comprising inverter AC voltage and DC voltage, are first analyzed. Then, methods for improving voltage stability, such as reactive power compensation, and the benefits and drawbacks of various compensation methods are investigated. Finally, the effect of reactive power compensation on frequency control stability is investigated and resolved. Simulations and experiments are used to validate the theory’s correctness.